The Role of Midwives in The Management OG High-Risk Pregnancy Care: Systematic Literature Review - Devy Lestari Nurul Aulia; Arum Dwi Anjani; Divani Salsa Billa; Selvi Andini Isna Ramadhani; Rini Rahmadhani; Aulia Rani; Yanti Febyola Purba; Nasha Aqeela (LPPM Universitas Harapan Bangsa, 2026)
High-risk pregnancy represents a condition that increases the likelihood of complications for both the mother and the fetus and therefore requires appropriate and comprehensive management. Midwives, as frontline healthcare providers, perform strategic roles in early detection, continuous monitoring, health education, and referral coordination in the management of high-risk pregnancies.This study analyzes the role of midwives in high-risk pregnancy care management using a Systematic Literature Review (SLR) approach. The review examined scientific articles retrieved from national and international databases, including Google Scholar, PubMed, ScienceDirect, SINTA, and Garuda. The search process identified 275 articles published between 2019 and 2025. Application of predefined inclusion and exclusion criteria resulted in the selection of 10 relevant articles for detailed analysis. The findings indicate that midwives contribute to the reduction of pregnancy complications and the improvement of maternal and neonatal safety through early detection of risk factors, routine monitoring of maternal and fetal conditions, provision of health education, and coordination of referral services. Continuity of midwifery care improves adherence to antenatal care visits and supports earlier management of pregnancy complications. Educational interventions delivered by midwives increase pregnant women’s knowledge, awareness, and healthy behaviors during pregnancy. Improved maternal understanding of pregnancy health contributes to prevention of delays in complication management and supports better pregnancy outcomes for both mothers and infants